Overcoming barriers of isolation in Distance Learning: Building a Collaborative Community in Learning - Mbukusa, Nchindo Richardson (Advances in Social Sciences Research Journal, 2017)
The rise in popularity of distance education programmes in a rural and remote Namibia poses challenges on students that are far removed from their colleagues, tutors and even their study materials. Interaction between the student and the study materials, tutors and peers are key challenges in open and distance learning. At the same time, sparsely populated areas of the country with less network coverage pose more challenges for web-based learning that could close up the gap. Using interviews, supported by this study engaged 5 groups of students (eight in each group) who have initiated collaborative groups while doing research studies at the Centre for External Studies, University of Namibia. The students are continuing with their educational endeavours through open and distance learning but who find themselves in areas that isolate them more from academic, administrative and logistics support. Their experiences of distance learning were investigated and three main themes emerged. These were academic and administrative challenges. Amongst many, the recommendations included: improving student-study materials contact, student-tutor contact and student-student contact (collaborative learning). Students do well when there is clear support from peers, tutors and the study materials that they interact with from day to day.